Guia (Algarve), gisement de vertébrés quaternaires à caractère saisonnier - Antunes, M. Telles (2010)
A vertebrate (Mammals, Reptiles, Amphibians) fauna From Guia (Algarve) is described. The site is the only one so far known in the «Faro-Quarteira sands». The fauna is upper Pleistocene in age (may even be younger). Its stratigraphical position shows it is younger than levels in the same unit that yielded mousterian/languedocian stone artifacts. A post Riss-Wurm age is admitted. The mammalian fauna nearly exclusively comprises small mammalremains; except for a few ones, only young individuals are represented. This unusual situation, coupled with data from the study of the Squamata and even more of the Amphibia, indicates that Guia locality corresponds to sedimentation in temporary, seasonal ponds originated in depressions in this sandy area during Winter and/or early Springtime.